Efficient removal of perfluorinated compounds from water using a regenerable magnetic activated carbon. (June 2019) - Meng, Pingping; Fang, Xiaolu; Maimaiti, Ayiguli; Yu, Gang; Deng, Shubo
Abstract: Adsorption by powder activated carbon (PAC) is recognized as an efficient method for the removal of perfluorinated compounds (PFCs) in water, while the poor separation of spent PAC makes it difficult for further regeneration, increasing the treatment cost significantly. In this study, an ultrafine magnetic activated carbon (MAC) consisting of Fe3 O4 and PAC was prepared by ball milling to remove PFCs from water efficiently. Increasing the percentage of Fe3 O4 and balling milling time decreased its adsorption capacity for perfluoroctane sulfonate (PFOS), whereas increased the magnetic separation property to some degree. The optimized MAC was prepared with a Fe3 O4 to PAC mass ratio of 1:3 after ball milling for 2 h, and the adsorption equilibriums of all the four PFCs on the optimal MAC were reached within less than 2 h, with the adsorption capacities of 1.63, 0.90, 0.33 and 0.21 mmol/g for PFOS, perfluorooctanoic acid (PFOA), perfluorohexane sulfonate (PFHxS) and perfluorobutane sulfonate (PFBS), respectively. Increasing the solution pH hindered the adsorption of PFOS significantly when the pH was less than the zero potential point (around 6) of the MAC, due to the decreased electrostatic attraction. The spent MAC could be easily separated with a magnet and regenerated by a small volume of methanol, and the regenerated MAC could be reused for more than 5 time and remain stable adsorption capacity for PFOS after 3 cycles. This study provides useful insights into the removal of PFCs by separable magnetic PAC in wastewater. Graphical abstract: Image 1 Highlights: Ultrafine magnetic activated carbon (MAC) was prepared by ball milling. All PFCs reached adsorption equilibrium on the MAC within less than 2 h. The MAC showed an adsorption capacity of 1.63 mmol/g for PFOS within 2 h. The magnetic MAC could be rapidly separated with a magnet. The spent MAC could be regenerated and reused for over 5 times.